Pengembangan E-Book Berbasis Pinterest “Pena Muhammad (Petualangan Nabi Muhammad)” Tentang Politik Rasulullah dalam Membangun Kota Madinah - Aeni, Ani Nur; Agustin, Dini; Putri, Mira Heryana; Ruhiyat, Ruhiyat (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study aims to produce an innovative and effective approach to learning Islamic Religion (PAI) at the elementary level through the use of a Pinterest-based e-book entitled